A new hybrid bonding technique: Adhesive-soft soldered joints - Kavak, N.; Altan, E. (SAGE PUBLICATIONS LTD, 2014)
Joining of components is usually accomplished by mechanical fastening, welding, or adhesive bonding. Apart from the classical methods, various hybrid methods applied with adhesives are widely used in industry to bond mechanical parts. This study describes a new hybrid bonding method as an alternative to currently used hybrid methods: adhesive-soft soldered joints. In this new hybrid technique, joints are made by adding various (5 wt%, 15 wt%, 25 wt%, and 50 wt%) amounts of soft soldering alloy powder into the adhesive at two different temperatures (180celcius and 200celcius). The strength of the joints is measured by tensile shear tests. The mechanical strength of adhesive joints carried out by adding soft soldering powder melted at 200celcius is higher than that of joints with only adhesives and unmelted soft soldering powders. The developed hybrid method is applied to attach the insert to cutting tools used in the machining industry and the feasibility of the method is investigated with experiments.
Keywords: soft solder; Adhesive; hybrid joint; lap-shear strength; MECHANICAL-PROPERTIES; STRENGTH; NANOCOMPOSITES; PERFORMANCE; FRICTION; MODEL; WEAR; Materials Science